How Can Vernacular Construction Techniques Sustain Earthquakes: The Case of the Bhatar Buildings - Carabbio, Raffaele; Pieraccini, Luca; Silvestri, Stefano; Schildkamp, Martijn (Frontiers in Built Environment, 2018)
After the 2005 M7.6 Kashmir earthquake (Pakistan), field observations reported that several buildings manufactured with local traditional techniques resisted well to that strong seismic event. In this paper the attention is focused on a typical vernacular construction technique commonly named as “Bhatar”, still practiced in the Himalayan regions of India and Pakistan. It is grounded upon the "timber lacing" or "timber reinforcement masonry" concept, i.e. the combination of dry-stacked loose stones with timber beams to increase the wall confinement. Despite its good seismic performances, it has still not been deeply studied from a structural engineering point of view. This paper represents a first attempt to fill this gap. It presents a full analytical study on the structural behaviour of a simple one-storey building unit characterized by a 3.6 m x 3.6 m square plan covered by an heavy wooden roof with 20 cm thick earth coverage, in order to investigate its response under gravity and seismic inertial loadings. Materials properties, static analysis and seismic analysis are discussed. In detail, Shorea Robusta wood and limestone rocks are identified as the most used construction materials for the Bhatar buildings. The Barton's model is applied to characterise the shear strength of the rubble stone layers in the wall. Static analysis reveals that normal stresses at the ground level are around 92 kPa, which can be considered acceptable for common soils. With respect to earthquake, the Bhatar technique can absorb wall cracking and distortion mechanisms, and can dissipate energy through friction between stones. Under the assumption of no vertical ground motion, the acceleration which activates in-plane sliding mechanisms is found to be around 0.5 g, being dependent on the interface friction between adjacent layers. Some preliminary considerations about the out-of-plane seismic behaviour are also provided concerning overturning and bending failure mechanisms. The results are based on assumptions taken by several authors and have not been verified with experimental tests. Nevertheless, some practical suggestions can be derived to improve the seismic shear strength and to ensure friction also in the case of significant vertical component of earthquake ground motions.